PERILAKU PERTAHANAN DERI KUMBANG KUYA MAS ASPIDOMORPHA SANCTAECRUCIS FABRICIUS (CHRYSOMELIDAE, CASSEDEVI) TERHADAP SEMUT PADA POMOEA CARNEA AUCT - Noerdjito, Woro A; Ito, Fuminori; Nakamura, Koji (BERITA BIOLOGI, 2000)
Ants are of high density on the host plant of golden tortoise beetle, Ipomoea carnea, and are being attracted by extrafloral nectaries on petiols.They are important predators of immature stages (eggs, larvae and pupae) of the beetles.The experiment was aimed to know how the golden tortoise beetles defense themselves against ants on I. carnea.The results indicated that golden tortoise beetle,both larvae and adults showed odd habits.They have a specific external organ, a protective camouflage with excreta of the larvae and oviposition strategy.The ant-beetle interaction on the host plants are discussed.